Pelayanan Pengujian Polyurethane Di Laboratorium Korosi dan Baterai Material Departemen Teknik Material dan Metalurgi FTIRS-ITS - Rohmannudin, Tubagus Noor; Sulistijono, Sulistijono; Amrulloh, M. Farian; Fachri, Muhammad (Jurnal KeDayMas: Kemitraan dan Pemberdayaan Masyarakat, 2024)
Polyurethane is a versatile polymeric material widely used as a substitute for rubber, metal, wood, and plastic due to its flexibility and multifunctional properties. To ensure the quality and reliability of polyurethane produced by the industry, the Corrosion and Battery Laboratory of the Department of Materials and Metallurgical Engineering at FTIRS-ITS conducted comprehensive testing. The tests included compression, shear, density, closed cell content (porosity), and thermal conductivity evaluations. The results showed that the polyurethane tested performed satisfactorily, exceeding the standard in several parameters. Compression testing yielded 2.46 kg/cm² compared to the standard of 2 kg/cm². Shear testing showed 6.63 kg/cm² against the standard of 4 kg/cm². Density testing recorded 49 kg/m³ with a standard of 45 kg/m³. The closed cell content test indicated 91.01% versus the standard of 90%. However, thermal conductivity testing showed 0.2 W/mK at 25°C, differing from the standard of 0.02 W/mK at 20°C. Overall, these results suggest that the tested polyurethane meets and exceeds most quality standards, demonstrating its reliability for various industrial applications. Through these tests, the Materials Chemistry Laboratory contributes to ensuring locally produced industrial products are competitive and reliable, as part of its community service efforts.